1997
DOI: 10.1002/hep.510250507
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical features and clinical course of antimitochondrial antibody-positive and -negative primary biliary cirrhosis

Abstract: Reports from North America and Northern Europe have suggested that antimitochondrial antibody (AMA) negative primary biliary cirrhosis (PBC) is a distinct chronic cholestatic liver disease with high prevalence of serum non‐organ‐specific autoantibodies other than AMA. To evaluate if such a peculiar serum immunoreactivity is associated with clinically relevant characteristics, we reviewed our experience with 297 Italian patients who have had a clinical and histological diagnosis of PBC and were regularly follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
1
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(171 citation statements)
references
References 16 publications
12
153
1
5
Order By: Relevance
“…In respect to the 23 patients who were AMA negative, but had abnormal LFTs and diagnostic liver histology, we feel that we are justified to include them because AMA-negative PBC is widely regarded as part of the spectrum of PBC. [11][12][13] Because of our case finding methods we may have underestimated the prevalence and proportion of AMA-negative PBC in our population.…”
Section: Discussionmentioning
confidence: 99%
“…In respect to the 23 patients who were AMA negative, but had abnormal LFTs and diagnostic liver histology, we feel that we are justified to include them because AMA-negative PBC is widely regarded as part of the spectrum of PBC. [11][12][13] Because of our case finding methods we may have underestimated the prevalence and proportion of AMA-negative PBC in our population.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Some patients in whom AMA are not detectable by conventional indirect immunofluorescence, may nevertheless be AMA positive when assessed by immunoblotting. 10,11 Furthermore, the use of cloned mitochondrial antigens such as triple hybrid recombinant molecule (r-MIT3) which contains the autoepitopes of PDC-E2, BCOADC-E2, and OGDC-E2 12 may identify AMA in the sera of patients previously thought to be AMA negative. Some patients labeled as having AMA-negative PBC, or ''autoimmune cholangitis,'' 6 may therefore be AMA positive rather than truly AMA negative.…”
Section: Ama-negative Pbc (Autoimmune Cholangitis) Is Probably the Samentioning
confidence: 99%
“…On the other hand, some forms ofAMA-negative PBCare believed to be a distinct clinical entity designated as autoimmune cholangitis (5-7). However, it is suggested that AMA-positive and AMA-negativePBCshare a similar clinical spectrum and outcome (8,9). The present paper describes a patient with AMA-negative PBCassociated with hyperthyroidism caused by painless thyroiditis.…”
Section: Introductionmentioning
confidence: 76%
“…Someauthors have found differential features, such as piecemeal necrosis, positive ASMA, higher serum aminotransferase levels, lower serum IgMlevels, and a benefical effect of prednisone and azathioprine in patients with autoimmunecholangitis (26). On the other hand, a similar clinical spectrum and a similar outcomeof the disease have been reported in AMA-negative and AMA-positive PBC, although different patterns of immunoreactivity are present in the two conditions (8,9). In the case presented here, normal serum aminotransferase levels and higher serum IgM levels were noted and serum ALPand y-GTP levels were improved with ursodeoxycholic acid.…”
Section: Discussionmentioning
confidence: 96%